PENGARUH PEMBELAJARAN BERBASIS MASALAH TERHADAP PRESTASI BELAJAR IPA SISWA KELAS IV SEKOLAH DASAR - Putu Beny Pradnyana; Desak Putu Anom Janawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research aimed at investigating the difference in science learning achievement between students studying through problem-based learning and those studying through conventional learning. 10 grade IV elementary school students were selected as research samples and they were divided into two groups: an experimental group and a control group. Those groups had been equalized by conducting Product moment analysis. This study utilized a post-test-only control group design. Learning achievement data were collected by using a multiple-choice test method. The test validity was examined by using Point Biserial while the test reliability was examined by using KR-20. Before testing the hypothesis, the data were processed with prerequisite test namely Normality Test (with a significance = 0.2), Variant Homogeneity Test (with a significance of 0.158), Box'M Test (with a significance = 0.146), and the Correlation Test between Dependent Variables / Multicollinearity (Tolerance and VIF =1). Then, the hypotheses were tested by using MANOVA (Multivariate Analysis of Variance). The research finding showed that: there was a significant difference in science learning achievement between students studying through problem-based learning and those studying through conventional learning (F=5.574 and sig.=0.046; p<0.05).